Earnings Management: analysis of powerful CEO in presence of social ties - Locatelli, Letícia Gomes (2021)
This study aimed to analyze the influence of powerful CEOs on earnings management (EM) considering the presence of social connections between the CEO and members of the board of directors (CA). The sample consisted of 183 Brazilian companies listed in [B]³ in the period 2011 to 2017, totaling 881 observations. EM was measured by the Jones (1991) and Modified Jones (1995) models and considered the dependent variable, under which the effect of (i) a CEO power metric developed by principal component analysis was analyzed from a multidimensional perspective of power (structural power, ownership power, power of specialization and power of prestige), (ii) an index that measures the level of social connections between the CEO and the Board members based on indicators already reviewed by the literature (educational, professional and family relationships background), and (iii) the interaction between these variables. The results of 6 linear regression estimates (MQO) with cross-section pools and robust errors indicate that powerful CEOs are related to higher levels of discretionary accruals, while social connections mitigate EM. When the interaction between these variables is included, both CEO power and social connections lose their significant effect on EM, indicating that in the presence of social connections, powerful CEOs may fail to engage in EM practices. This result contributes to the discussion about the interference of social factors on economic decisions, drawing attention to the impact of social factors on the quality of profits and the CG of companies.